Upaya Penurunan Lembur Departemen Parts, Apparel, dan Accessoris - Oentoro, Golden Suryajaya; Yang, Debora Anne (Jurnal Titra, 2015)
CV. Roda Lintas Khatulistiwa is a subsidiary of PT. Insera Sena to handle for retail and distribute accessoris, supplies, and bicycle part. CV. Roda Lintas Khatulistiwa has parts, appareal and accessories department(PAA) to handle distribution of goods to all retailers. Goods are handled PAA department can be classified into 4 types, plastic, cardboard, staples packing products, and non-packing. Problems that occur in PAA department is the overtime with an average of 27.5 hours per month. Calculation of standard time taken to obtain a production capacity of PAA department. The capacity results compared to actual production PAA department and it is known that the capacity is smaller than the number of actual production, so it is necessary to increase production capacity. Efforts are being made, like the analysis of motion studies to reduce cycle time with the help of two hands process chart, the replacement of certain kinds of packing items, and eliminate the barcoding process for non-packing product improvement effort is shown to lead to total savings of approximately 13 working days 20 hours 8 minutes 47 seconds.